Membangun Desa Mandiri Pupuk Berbasis Zero Waste Sebagai Upaya Peningkatan Taraf Hidup Masyarakat Kecamatan Anggrek Kabupaten Gorontalo Utara - Syamsul Bahri; Nurmi Nurmi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
The increased production of agriculture to meet food needs faces a major challenge in developing environmentally-friendly fertilizer. This activity is aimed at educating crop cultivation and training in the technology of crop growing (organic fertilizers), assisting covid-19 disease prevention programs and helping undergrowth programs primarily related to the scientific discipline of each project student in the "village builds" village. Where the activity is carried out by plants that have a potential for crop development, it has both land support and crop waste as raw organic fertilizer. The methods of producing organic fertilizer use the fermentation method using the raw materials of livestock waste and plant waste. Organic fertilizer is done by the way all the material is distributed evenly and into the compost container. The inundation takes place within 21 days, where each week it is inverted until the milling process can take place properly. Based on the results it has been concluded that the production of organic fertilizer in the seedlings can be an alternative provider of fertilizer for farmers.